UNRAVELING THE GENETIC AND EPIGENETIC LANDSCAPE OF RHEUMATOID ARTHRITIS: A COMPREHENSIVE REVIEW OF PATHOGENESIS, DIAGNOSIS, AND THERAPEUTIC IMPLICATIONS - Mendonça, Juliana Coimbra de; Almeida, Mariana Melo; Maronese, Francesco; Destefani, Afrânio Côgo; Destefani, Vinícius Côgo (Revista Ibero-Americana de Humanidades, Ciências e Educação, 2024)
This exhaustive review delves into the genetic and epigenetic foundations of Rheumatoid Arthritis (RA), a multifaceted autoimmune disorder characterized by persistent joint inflammation. We discuss the findings of genome-wide association studies (GWAS) that have uncovered numerous genetic loci associated with RA, emphasizing the substantial impact of HLA variants on disease susceptibility and severity. The review also explores epigenetic mechanisms such as DNA methylation, histone modifications, and the regulatory role of microRNAs, all of which influence gene expression and immune response in RA. The involvement of inflammasomes in mediating inflammatory responses emphasizes potential therapeutic targets. Furthermore, the application of artificial intelligence for analyzing intricate genetic data presents promising opportunities for advancing diagnosis and treatment strategies. This article underscores the critical need for integrating multi-omics data. It emphasizes the significance of collaborative research in the field of RA, highlighting the importance of your work in this area.